R-CPT interface for the automation and improvement of seasonal forecasts - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A prototype of the R-CPT tool was piloted in early 2020 and by mid-year was officially released in Honduras. It now works in an operational manner within the meteorological service.